Genetic diversity, reproductive performance, and genetic enhancement strategies in Huang-Huai goats - Kai Quan; Huibin Shi; Caihong Wei; Jun Li; Kun Liu; Huihua Wang; Wei Sun; Haoyuan Han (Frontiers in Genetics)
The Huang-huai goat, indigenous to China’s Huang-Huai Plain, is celebrated for its exceptional reproductive capacity, succulent meat, and superior leather qualities. The Huang-huai goat’s reproductive characteristics, genetic diversity, and the genetic underpinnings of intersexuality, aiming to inform conservation efforts and genetic resource management. Our study at the Huang-huai Goat Science and Technology R&D Center monitored 600–800 female goats and 16–24 male goats from June 2020 to May 2022, adhering to NIH guidelines and with ethical approval from Henan University of Animal Husbandry and Economics. Our findings indicate that these goats exhibit a year-round estrus cycle averaging 19–23 days, a gestation period of 146–150 days, and an average litter size of 2.74, with an annual reproduction rate of 418.96% and a weaning survival rate of 94.75%. Transcriptome sequencing identified eleven candidate genes associated with multiple offspring, including PTX3, MMP13, and NR4A1, which play roles in organ development and hormonal regulation. SNP analysis revealed specific genotypes in GJB6 and PRKAA1 linked to higher lambing numbers, offering molecular markers for selective breeding. The study also highlighted the role of the Polled Intersex Syndrome (PIS) locus in causing both hornless and intersexual traits, emphasizing the importance of genetic screening for maintaining breed health and productivity. The genetic resources of the Huang-huai goat, recognized as a national geographical indication product, are vital for the livestock industry and require strategic conservation for sustainable development. This review highlights the importance of preserving and utilizing the genetic resources of the Huang-huai goat to enhance its contribution to agriculture.